Understanding the process of psychological development in youth athletes attending an intensive wrestling camp - Pierce, S.; Gould, D.; Cowburn, I.; Driska, A. (Qualitative Research in Sport, Exercise and Health, 2016)
This study used a grounded theory methodology to understand if and how psychological development in youth athletes was facilitated by an `intensive` summer wrestling camp experience. The theoretical sampling approach involved 10 athlete participants of the camp, nine parents of athletes, the director of the camp, and four camp staff members, who took part in a series of interviews before, during, and after the camp. Two researchers were also embedded in the camp and attended all sessions, took detailed notes, collected camp materials, and conducted observations. Following a grounded theory analysis approach, a model is presented that outlines how youth participants` developed psychological qualities from the coach-created challenges and adversity that were systematically designed to facilitate sport performance enhancement and life skills. Variations emerged in psychological antecedents and characteristics, how the challenging wrestling camp environment was interpreted and experienced, and how learning was transferred to sport and life domains outside of the wrestling camp. This study provided insight into a unique youth sport context that was able to simultaneously develop psychological qualities to be used as sport performance enhancement and life skills.